1998
DOI: 10.2176/nmc.38.805
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Fasudil Hydrochloride and Ozagrel Sodium for Cerebral Vasospasm Following Aneurysmal Subarachnoid Hemorrhage

Abstract: Fasudil hydrochloride is a new type of intracellular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…8) These results suggest that a combination therapy consisting of fasudil and ozagrel has superior efficacy for treating SAH patients. However, the present results indicated that the combination of fasudil plus ozagrel did not result in better efficacy than fasudil only.…”
Section: Efficacymentioning
confidence: 84%
See 1 more Smart Citation
“…8) These results suggest that a combination therapy consisting of fasudil and ozagrel has superior efficacy for treating SAH patients. However, the present results indicated that the combination of fasudil plus ozagrel did not result in better efficacy than fasudil only.…”
Section: Efficacymentioning
confidence: 84%
“…2) Combination therapy using fasudil and ozagrel is reported to be effective. 8) The present sub-analysis of the fasudil PMS study compared the safety and efficacy of the combination of fasudil plus ozagrel with fasudil only to assess the interactions between fasudil and ozagrel in a large number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fasudil probably can move through the retina to inhibit rod axon terminals. Although fasudil originally was used for cerebral vasospasm, 33 intravitreal fasudil already has been applied to patients with diabetic macular edema and optic nerve damage to successfully interrupt vascular pathology. 34,35 Intravitreal injections of fasudil (10 μM) in patients showed no evidence of intraocular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical use of ROCK inhibitors is currently limited to the suppression of vascular constriction (Fujita et al, 2010), our recent data suggest that ILC with mutant E-cadherin (in contrast to E-cadherin-negative IDC) depend on ROCK signaling for the formation and dissemination of tumors (Schackmann et al, 2011). These findings might pave the way for clinical inhibition of ROCK signaling in specific tumor subtypes such as ILC using already clinically approved inhibitors, for instance fasudil (Nakashima et al, 1998). In such a setting, breast cancer patients with mutant E-cadherin and cytosolic p120 could be treated with ROCK inhibitors.…”
Section: Future Directions and Clinical Implicationsmentioning
confidence: 96%